2020
DOI: 10.1001/jamanetworkopen.2020.15756
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of Universal and Targeted Hepatitis C Virus Screening in the United States

Abstract: Key Points Question Are universal hepatitis C virus (HCV) screening for all US adults aged 18 years or older and targeted HCV screening among people who inject drugs cost-effective for limiting HCV infection? Findings In this economic evaluation study, HCV screening for people who inject drugs in the US increased quality-adjusted life-years (QALYs) by 0.23 (ie, approximately 3 months), with an incremental cost-effectiveness ratio of $45 465 per QALY. Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 58 publications
1
22
0
3
Order By: Relevance
“…A Japanese study reached a similar conclusion that the GLE/PIB regimen is the best strategy among the four DAA regimens (7). In the US, the GLE/ PIB regimen is considered a better value-for-money DAA than its predecessors (39). Similar to the above studies, our findings suggest that the GLE/PIB regimen is cost-effective in Chinese patients.…”
Section: Discussionsupporting
confidence: 85%
“…A Japanese study reached a similar conclusion that the GLE/PIB regimen is the best strategy among the four DAA regimens (7). In the US, the GLE/ PIB regimen is considered a better value-for-money DAA than its predecessors (39). Similar to the above studies, our findings suggest that the GLE/PIB regimen is cost-effective in Chinese patients.…”
Section: Discussionsupporting
confidence: 85%
“…They estimated cost effectiveness comparing screening programs targeting PWIDs with the universal screening of United States adults. They concluded that HCV screening for PWIDs could potentially decrease the risk of untreated HCV infection and liver-related mortality and may thus be cost effective[ 410 ].…”
Section: Who Really Needs Treatment: the Proposed Policymentioning
confidence: 99%
“…intravenous drug users) and highly effective DAA treatments have also proven cost-effective in avoiding liver-related mortality and liver transplantations. 112 There are three targets of DAA therapy, including NS3/4A protease inhibitors, NS5A polymerase inhibitors, NS5B polymerase inhibitors. DAA therapy is highly effective, with SVR rates >95% in genotype 1-infected patients without cirrhosis including those co-infected with human immunodeficiency virus, and about 78–87% effective in decompensated cirrhotics with Child–Turcotte–Pugh class C disease.…”
Section: Hepatitis Cmentioning
confidence: 99%